Safely managed drinking water around the world - Mora-Alvarado, Darner (2024)
This study addresses the concept of “Safely Managed Drinking Water” (APGFS) in the world by 2022. This new concept is an advance when moving from the MDGs (1990-2015) to the SDGs (2016-2030) and is defined as “Water for consumption from an improved source located inside the home or in the patio or plot, available when necessary and free of feacal contamination and priority chemical substances.” Based on this definition, the APGFS data from the report “Progress on Drinking Water, Sanitation and Hygiene: 2000-2022” published in 2023 is addressed and analyzed. The results show that 51% of the countries, territories and areas report data coverage with APGFS; However, of the 131 nations - without counting the areas or territories - 48.10% of the coverage data agree with the coverage of services free of priority feacal and chemical contamination, but 68 countries (51.90%) presented superior coverage in water free of drinking contamination, those free of physicochemical and microbiological contamination, without using the APGFS concept. But the most serious thing is that at least 49% of the nations studied do not provide water quality data. Finally, the non-specificity of the conceptualization of the indicators proposed by the Joint Monitoring Program allows countries to give them different interpretations, according to their possibility of information or convenience, affecting the comparison of data.